O consumo de joias e a construção da identidade de gênero : muito além do simples consumo - Garcia, Victor Corrêa (2018)
Consumption is part of everyday life for most subjects. Every day not only physical goods are consumed, but also intellectual, social, cultural and other types of goods. The goods are endowed of meaning and are consumed and used to outsource the wills, wi